Clinical and Technical Guideline for Endoscopic Ultrasound (EUS)-Guided Tissue Acquisition of Pancreatic Solid Tumor: Korean Society of Gastrointestinal Endoscopy (KSGE) - Chung, Moon Jae (Clin Endosc, 2021)
Endoscopic ultrasound (EUS)-guided tissue acquisition of pancreatic solid tumor requires a strict recommendation for its proper use in clinical practice because of its technical difficulty and invasiveness. The Korean Society of Gastrointestinal Endoscopy (KSGE) appointed a Task Force to draft clinical practice guidelines for EUS-guided tissue acquisition of pancreatic solid tumor. The strength of recommendation and the level of evidence for each statement were graded according to the Minds Handbook for Clinical Practice Guideline Development 2014. The committee, comprising a development panel of 16 endosonographers and an expert on guideline development methodology, developed 12 evidence-based recommendations in 8 categories intended to help physicians make evidence-based clinical judgments with regard to the diagnosis of pancreatic solid tumor. This clinical practice guideline discusses EUS-guided sampling in pancreatic solid tumor and makes recommendations on circumstances that warrant its use, technical issues related to maximizing the diagnostic yield (e.g., needle type, needle diameter, adequate number of needle passes, sample obtaining techniques, and methods of specimen processing), adverse events of EUS-guided tissue acquisition, and learning-related issues. This guideline was reviewed by external experts and suggests best practices recommended based on the evidence available at the time of preparation. This guideline may not be applicable for all clinical situations and should be interpreted in light of specific situations and the availability of resources. It will be revised as necessary to cover progress and changes in technology and evidence from clinical practice.